Assessment of Water Storage to Socio-environment Impacts and Inundation Mapping under Dam Height Variations in Sunkoshi III Hydropower Project, Nepal - Prajapati, Raghu Nath; Gubhaju, Abhishek; K.C., Anshu; Khatri, Krishna Raj; Awale, Madan; Chaudhary, Sristi (Journal of Engineering Issues and Solutions, 2026)
Hydropower development in the mountainous regions of Nepal requires thorough assessments of both technical feasibility and socio-environmental impacts. This study looks at how different dam heights affect water storage for the proposed Sunkoshi III Hydropower Project. It focuses on inundation mapping and the socio-environmental consequences that follow. By using GIS-based spatial analysis along with demographic data from ten municipalities that will be affected, we modeled how much area would be inundated at water levels between 664 meters and 734 meters. The findings show that as water levels rise, there is a quick increase in the area submerged, the volume of water, the number of displaced households, flooded farmland, and damage to roads. At the highest water level in 734 m, over 37 million square meters of land would be underwater, around 3,825 households and 3.7 million square meters of farmland are impacted. The population at risk includes residents from more than ten municipalities, with the greatest exposure observed in Chautara, Sangachok Gadhi and Indrawati areas.